Examining the interplay of teacher well-being, executive function, and adaptability in virtual instruction during COVID-19 disruptions - Garcia, Aileen S.; Jeon, Shinyoung; Kwon, Kyong-Ah; Horm, Diane M. (Frontiers in Education, 2024)
The documented challenges of the early care and education (ECE) workforce include poor well-being, inadequate compensation, and high turnover rates. The COVID-19 pandemic not only exacerbated these issues, but also imposed additional demands such as virtual instruction, highlighting the need to understand how teachers’ well-being relates to their adaptability in teaching. The present study examined whether early childhood teachers’ well-being is directly and indirectly related to adaptability to virtual instruction via teachers’ executive function during the COVID-19 pandemic. With a research-practice partnership project in a Head Start program in a metropolitan area in the central United States, data were collected from the Early Head Start/Head Start annual teacher survey (n = 148). Mediation analysis showed that teachers who demonstrated higher well-being displayed higher levels of executive function, which in turn was associated with greater adaptability in virtual instruction. Beyond the pandemic, findings highlight the importance of supporting teachers’ well-being and executive functions to promote adaptability, which is critical not only in virtual instruction, but also in successfully navigating other challenges of the teaching profession.